Softepigen : Primers design web-based tool for MS-HRM technique (2018)
Polymerase Chain Reaction (PCR) based techniques for DNA methylation techniques includes MS-HRM technique. Methylation Sensitive High-Resolution Melting (MS-HRM) primer-design requires a set of necessary recommendations for such DNA methylation assessment. However, there were not any available software that allows an automatic design of this kind primers. We present Softepigen, the first complete MS-HRM primer design software. Softepigen allows to search for primers in a genomic region following Wojdacz's recommendations and targets primer binding regions with high linguistic complexity sequences that increase the specificity of the converted sequence of the human genome. We performed in-silico PCR analysis through BiSearch ePCR tool to validate the specificity of the of the primers designed using Softepigen. Softepigen for MS-HRM performance in our genomic regions of interest show satisfactory specificity measurements, and we implemented it for freely available use in web-based interface in www.soft-epigen.com.